Mechanical Properties and Acoustic Emission Characteristics of Weakly Cemented Sandstone With Different Grain Sizes - Liu, Bin; Zhang, Tong; Zhang, Hongwei; Yuan, Qiupeng (Frontiers in Earth Science, 2022)
The weakly cemented sandstone is widely distributed in the Western Mining Area, which is mainly formed by mineral grains and cemented minerals through compaction and cementation. To study the influence of grain size on the mechanical properties and acoustic emission (AE) characteristics of weakly cemented sandstone, uniaxial compression and Brazilian splitting AE tests were carried out on four weakly cemented sandstone specimens with different grain sizes. The physical properties, mechanical behaviors, and AE characteristics of sandstone under two conditions were analyzed, and the microfailure mechanism was investigated. The results show that the P-wave velocity, density, uniaxial compressive strength (UCS), and tensile strength of weakly cemented sandstones with different grain sizes decrease with the increase of grain size. The medium sandstone and coarse sandstone exhibit ductile failure, while the siltstone and fine sandstone exhibit brittle failure under the two conditions. The distribution of AE signal strength is nearly Gaussian in the time domain. The peak frequency and upper limit of signal strength are negatively correlated with grain size, and the occurrences of lots of high-strength AE signals can be used as the precursor of sandstone failure. The damage evolution shows the trend of low-speed damage-accelerated damage-low-speed damage, and the damage increase at the peak load is negatively related to the grain size. The microfailure mechanism is the tension-shear mixed failure, which is dominated by tensile failure, with few shear failures. The proportion of shear cracks is positively correlated with the grain size under uniaxial compression, while there is no significant correlation between shear cracks and grain size under Brazilian splitting.